Gut Dysbiosis and Diabetic Foot Ulcer: Role of Probiotics - Ankit Awasthi; Leander Corrie; Sukriti Vishwas; Monica Gulati; Bimlesh Kumar; Dinesh Kumar Chellappan; Gaurav Gupta; Rajaraman D. Eri; Kamal Dua; Sachin Kumar Singh (Pharmaceutics, 2022)
Diabetic foot ulcer (DFU) is a multifactorial disease and one of the complications of diabetes. The global burden of DFU in the health sector is increasing at a tremendous rate due to its cost management related to hospitalization, medical costs and foot amputation. Hence, to manage DFU/DWs, various attempts have been made, including treating wounds systematically/topically using synthetic drugs, herbal drugs, or tissue engineering based surgical dressings. However, less attention has been paid to the intrinsic factors that are also the leading cause of diabetes mellitus (DM) and its complications. One such factor is gut dysbiosis, which is one of the major causes of enhancing the counts of Gram-negative bacteria. These bacteria produce lipopolysaccharides, which are a major contributing factor toward insulin resistance and inflammation due to the generation of oxidative stress and immunopathy. These all lead to DM and DFU. Probiotics are the commercial form of beneficial gut microbes that are taken as nutraceuticals by people of all ages to improve gut immunity and prevent gut dysbiosis. However, the role of probiotics has been less explored in the management of DFU. Hence, the therapeutic potential of probiotics in managing DFU is fully described in the current review. This report covers the linkage between gut dysbiosis and DFU, sources of probiotics, the mechanisms of probiotics in DW healing, and the impact of probiotic supplementation in treating DFU. In addition, techniques for the stabilization of probiotics, market status, and patents related to probiotics have been also covered. The relevant data were gathered from PubMed, Scopus, Taylor and Francis, Science Direct, and Google Scholar. Our systematic review discusses the utilization of probiotic supplementation as a nutraceutical for the management of DFU.